Variability in usual care mechanical ventilation for pediatric Acute Respiratory Distress Syndrome: Time for a decision support protocol? - Newth, Christopher J.L. (Pediatr Crit Care Med, 2017)
OBJECTIVE: Although pediatric intensivists philosophically embrace lung protective ventilation for Acute Lung Injury (ALI) and Acute Respiratory Distress Syndrome (ARDS), we hypothesized that ventilator management varies. We assessed ventilator management by evaluating changes to ventilator settings in response to blood gases, pulse oximetry or end tidal CO(2). We also assessed the potential impact that a pediatric mechanical ventilation (MV) protocol adapted from NHLBI ARDSNet protocols could have on reducing variability by comparing actual changes in ventilator settings to those recommended by the protocol. DESIGN: Prospective observational study. SETTING: Eight tertiary care US PICUs, October 2011 – April 2012. PATIENTS: 120 patients (age range 17 days to 18 years) with ALI/ARDS. MEASUREMENTS AND MAIN RESULTS: 2100 arterial and capillary blood gases, 3964 SpO(2) and 2757 PETCO(2) values were associated with 3983 ventilator settings. Ventilation mode at study onset was Pressure Control (PC) 60%, Volume Control (VC) 19%, Pressure-regulated Volume Control (PRVC) 18%, High Frequency Oscillatory Ventilation (HFOV) 3%. Clinicians changed FiO(2) by ±5 or ±10% increments every 8 hours. PEEP was limited at ~10 cmH(2)0 as oxygenation worsened, lower than would have been recommended by the protocol. In the first 72 hours of MV, maximum tidal volume/kg using predicted versus actual body weight was 10.3 ml/kg; 8.5–12.9 (median; IQR) versus 9.2 ml/kg; 7.6–12.0 (p<0.001). Intensivists made changes similar to protocol recommendations 29% of the time, opposite the protocol’s recommendation 12% of the time and no changes 56% of the time. CONCLUSIONS: Ventilator management varies substantially in children with ARDS. Opportunities exist to minimize variability and potentially injurious ventilator settings by utilizing a pediatric mechanical ventilation protocol offering adequately explicit instructions for given clinical situations. An accepted protocol could also reduce confounding by MV management in a clinical trial.